Corrosion protection of low carbon steel by conducting terpolymer nanocomposite coating in 3.5 wt% NaCl solution. Issue 4 (16th February 2020) - Aslam, Jeenat; Mobin, Mohammad; Aslam, Ruby; Ansar, Farina
Abstract: A terpolymer (TP) comprising of aniline (ANi), o-toluidine (OTd) and o-aminobenzoic acid (OAc), and its nanocomposite (NCs) with TiO2 nanoparticles (NPs) (TP-TiO2 -NCs) were prepared through in situ chemical oxidative polymerization exploiting an oxidant (ammonium persulphate) and external dopant (hydrochloric acid). NCs of respective homopolymers with TiO2 -NPs, namely ANi-TiO2 -NCs, OTd-TiO2 -NCs and OAc-TiO2 –NCs were also synthesized in accordance with an identical process. FT-IR, XRD, SEM and TEM were employed to characterize the prepared compounds. For the preparation of the coatings, various synthesized compounds were separately dissolved in N-methyl-2-pyrrolidone and casted on low carbon steel (LCS) coupons. The adhesion property of coatings to the metal substrate was also studied. The anticorrosion behavior of LCS specimens coated with different polymers was evaluated in 3.5 wt% NaCl solution at 30 °C using open circuit potential (OCP), potentiodynamic polarization (PDP), electrochemical impedance spectroscopy (EIS) and scanning electron microscopy (SEM). The anticorrosion properties of TP-TiO2 -NCs were compared with that of TP and homopolymer NCs. The coatings surface morphology, prior to and after prolonged immersion (2 months) in corrosive solution, was evaluated using SEM. Under identical experimental conditions, TP-TiO2 -NCs coating provides better anticorrosion performance than individual homopolymer NCs and pure TP coatings.